GMMTV’s Integrated Marketing Communications (IMC) Strategy for Market Expansion in Indonesia, 2020–2025 - Tsabita, Khansa; Prameswari, Theresia Yola; Purbantina, Adiasri Putri (LPPM Universitas PGRI Adi Buana Surabaya, 2026)
GMMTV, a Thai entertainment company, excels at global digital content marketing and strategically targets Indonesia. This study analyzes GMMTV’s Integrated Marketing Communication (IMC) strategy for marketing its entertainment products in Indonesia, a Southeast Asian country. The study adopts a descriptive qualitative approach, using secondary data such as official social media posts, Indonesian mass media reports, documentation of promotional activities, audience interactions on digital platforms, and official merchandise materials. Guided by the IMC concept from Kotler and Keller, the research method involves systematically identifying and interpreting how the six IMC components (advertising; online, social media, and mobile communication; events and experiences; word of mouth; publicity and public relations; and packaging) are applied. The results show varying degrees of localization among these components. The strategies emphasize digital media optimization, audience experience, and public exposure in Indonesia, while packaging remains generic and targets the global market. Overall, these findings indicate that GMMTV employs an adaptive marketing communication approach across multiple channels for Indonesian audiences.